Meltwater flow through a rapidly deglaciating glacier and foreland catchment system: Virkisjökull, SE Iceland - Flett, Verity; Maurice, Louise; Finlayson, Andrew; Black, Andrew; MacDonald, Alan; Everest, Jez; Kirkbride, Martin (Hydrology Research, 2017)
The aim of this study is to characterise the glacial and pro-glacial hydrology of a rapidly de-glaciating system at Virkísjökull in SE Iceland, and to determine the water velocities through the glacier and pro-glacial area. This was achieved using dye tracer tests, river discharge measurements and studies of conduits within the foreland and lower glacial ablation zone using Ground Penetrating Radar (GPR). Tracer testing through the glacier via a moulin demonstrated rapid flow of 0.58 m s-1 which is comparable to the flow velocities within the pro-glacial river. A subsequent test at the end of the winter season demonstrated slower but still rapid flow of 0.02 m s-1. A tracer test through the proglacial foreland shows that the large proglacial lake does not substantially attenuate flow, with velocities of 0.03 m s-1. GPR profiles suggest the presence of a buried conduit system enabling the rapid transit of water through this area. The pro-glacial foreland contains buried ice which represents the remains of the retreating glacier; therefore this conduit system may be the remains of an en- and sub-glacial conduit flow-path. Buried conduits may be common in other de-glaciating ice cored forelands, and this study reveals that these may by-pass large proglacial lakes, which has implications for understanding hydrological response times in glacial catchments. The pro-glacial river is highly responsive to melt as a result of the fully developed conduits in both the sub-glacial and pro-glacial areas. Flow in the river is perennial, suggesting that the conduit systems in the glacier and buried ice remain open and active all year, and that glacial melting occurs in winter as well as in summer, enhancing the rapid deglaciation.